INOVASI TEKNOLOGI DAN INOVASI KELEMBAGAAN MENDUKUNG KEBERLANJUTAN USAHATANI LADA DI KALIMANTAN TIMUR / Technology and Institution Innovation Supporting the Sustainability of Pepper Farming System in East Kalimantan - Agus Wahyudi; Suci Wulandari (Jurnal Penelitian Tanaman Industri, 2019)
Pepper farming in East Kalimantan has faced many obstacles. It is shown by the decline in pepper production in the last five years and the pepper conversion. This condition will affect the sustainability of pepper farming in East Kalimantan, as one of the national white pepper centers. Consequently, it is important to analyze and to establish a technology and institutional innovations. The study aimed to: (1) measure and analyze the sustainability of pepper farming, (2) identify technology innovation, (3) map the opportunities for adoption, and (4) develop institutional innovation and support system. The sustainability analysis of farming was done using weighting and rating methods. Data were collected in Kutai Kertanegara Regency, East Kalimantan in 2016. Results showed that the sustainability level of pepper farming is 3.0062, in the good category, but with a very low value. The environmental aspects provided the greatest value of the contribution to sustainability, followed by economic aspects and social aspects. Technology innovation was needed to overcome the problems. Nevertheless, technology adoption was relatively low. This was influenced by several factors, such as economic factors namely costs and income, social factors namely institutions and facilities support, and technological factors namely suitability and ease of implementation. Therefore, technology innovation needs to be supported by institutional innovation. The types of institutional innovations consist of: (1) establishment of working groups, (2) development of Seed Self-Reliance Region, (3) regulations related to quality standards and monitoring mechanisms, and (4) joint sales, as well as supporting facility to accelerate innovation adoption.Keyword: sustainability index, technology adoption, economic, support facilities. AbstrakUsahatani lada di Kalimantan Timur masih dihadapkan pada berbagai permasalahan, yang ditunjukkan oleh penurunan kemampuan produksi setelah lima tahun dan adanya konversi usahatani dari lada menjadi komoditas lain. Hal ini akan mempengaruhi keberlanjutan usahatani lada di Kalimantan Timur sebagai salah satu sentra lada putih nasional. Oleh karena itu penting untuk dianalisis dan disusun inovasi teknologi dan kelembagaan untuk mengatasinya. Kajian bertujuan untuk (1) mengukur dan menganalisis keberlanjutan usahatani lada, (2) identifikasi inovasi teknologi, (3) pemetaan peluang adopsi, serta (4) menyusun inovasi kelembagaan dan dukungan bagi peningkatan adopsi inovasi. Analisis keberlanjutan usahatani dilakukan dengan menggunakan metode weighting dan rating. Pengambilan data dilakukan di Kabupaten Kutai Kertanegara Kalimantan Timur pada tahun 2016. Berdasarkan analisis yang dilakukan, diketahui bahwa tingkat keberlanjutan usahatani lada memiliki nilai 3,0062 masuk kategori baik, namun dengan nilai sangat rendah pada kelas tersebut. Aspek lingkungan memberikan nilai kontribusi terbesar terhadap keberlanjutan, diikuti dengan aspek ekonomi dan aspek sosial. Inovasi teknologi diperlukan untuk mengatasi permasalahan sehingga terbangun keberlanjutan usahatani lada. Secara umum, peluang adopsi teknologi masih relatif rendah.  Hal ini dipengaruhi oleh beberapa faktor yaitu faktor ekonomi yaitu dari sisi biaya dan pendapatan, faktor sosial yaitu kelembagaan dan dukungan fasilitas, serta faktor teknologi yaitu kesesuaian dan kemudahan dalam menerapkan teknologi. Oleh karena itu inovasi teknologi perlu didukung dengan inovasi kelembagaan. Jenis inovasi kelembagaan bagi peningkatan keberlanjutan usahatani lada yaitu: (1) pembentukan kelompok kerja, (2) pengembangan desa mandiri benih, (3) regulasi terkait standar mutu dan mekanisme pengawasan, serta (4) penjualan bersama, Selain itu juga perlu dukungan fasilitas untuk mempercepat adopsi inovasi.Kata kunci: indeks keberlanjutan, adopsi teknologi, ekonomi, fasilitas pendukung.